Protective effect of juwet fruit extract (Syzygium cumini L.) on duodenum histomorphometry and histopathology of male mice exposed to pyrantel pamoate - Susilowati, Rina Priastini; Santoso, Adit Widodo; Sabini, Jasmine Harumi (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2024)
Pyrantel pamoate, known as an anthelmintic under the brand name Combantrin®, is effectively used to kill worms in the intestines. However, long-term use of it has been associated with side effects and risk of drug resistance. Syzygium cumini L.is known for its antioxidant and anti-inflammatory which may support antiparasitic effects and tissue healing. This study aims to examine the effect of juwet (S. cumini L.) fruit water extract (JFWE) on the duodenum structure of mice suspected to be infected with worm, through histomorphometric analysis and histopathological examination. The pyrantel pamoate was only administered once after the acclimatization period, while the JFWE was administered for 3 weeks. A total of 30 male mice were divided into six groups: negative control (aquadest), positive control (pyrantel pamoate, Combantrin® 20 mg/mL), and JFWE at doses of 5 mg/mL, 10 mg/mL, 20 mg/mL, and 40 mg/mL, administered for 3 weeks. Histomorphometric and histopathological evaluations were conducted by microscopically observing the duodenum structures, including intestinal villi, and the thickness of the mucosa, submucosa, and muscularis layers. The results showed a significant difference for the decrease in intestinal villi height and thickness of the mucosa, submucosa, and muscularis layers in JWFE doses of 5 mg/mL and 10 mg/mL administration group, compared to the negative control group (aquadest), the treatment groups of pyrantel pamoate, and JFWE doses of 20 mg/mL and 40 mg/mL (p<0.05). The conclusion is that the administration of juwet fruit water extract doses of 20 mg/mL and 40 mg/mL can improve the histomorphometry structure and also the histopathology of the duodenum of male mice.